2015
DOI: 10.1080/01635581.2015.1082108
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Inflammatory Index and Risk of Esophageal Squamous Cell Cancer in a Case-Control Study from Iran

Abstract: Background Diet and inflammation have been suggested to be important risk factors for esophageal squamous cell carcinoma (ESCC). In this study, we examined the ability of the dietary inflammatory index (DII) to predict ESCC in a case-control study conducted in Iran. Methods This study included 47 ESCC cases and 96 controls hospitalized for acute non-neoplastic diseases. The DII was computed based on dietary intake assessed by a previously validated food frequency questionnaire. Logistic regression models wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 47 publications
2
48
0
Order By: Relevance
“…In a previous case-control study conducted in the same catchment area in which this study was based, we found that higher consumption of total fat, oleic acid, saturated fat, total PUFA, trans fat, MUFA, and linoleic acid were significantly associated with increased risk for UC; however, no statistically significant association was detected between the risk of UC and intake of n-3 PUFAs or cholesterol (23). Previously, the DII has been shown to be associated with reduced bone mineral density (24) and esophageal squamous cell cancer (25) in similar Iranian populations.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous case-control study conducted in the same catchment area in which this study was based, we found that higher consumption of total fat, oleic acid, saturated fat, total PUFA, trans fat, MUFA, and linoleic acid were significantly associated with increased risk for UC; however, no statistically significant association was detected between the risk of UC and intake of n-3 PUFAs or cholesterol (23). Previously, the DII has been shown to be associated with reduced bone mineral density (24) and esophageal squamous cell cancer (25) in similar Iranian populations.…”
Section: Discussionmentioning
confidence: 99%
“…The DII also has been associated with a variety of cancers, including: colorectal and esophageal cancers [1924] and, among urological cancers, with increased risk of prostate and bladder cancers [2528]. In the Iowa Women’s Health Study (IWHS), the DII has been shown to be associated with colorectal and breast cancer incidence [29, 30] and mortality [31].…”
Section: Introductionmentioning
confidence: 99%
“…High scores of this DII have been positively associated with a variety of cancers, including colorectal cancer (17, 18), and esophageal cancer (1921) and, among urological cancers, prostate (22, 23), bladder cancers (24) renal cancer (25) and urothelial cancer (26). Using this case-control study conducted in Italy (27), this is the first attempt to examine the association between the DII and RCC risk.…”
Section: Introductionmentioning
confidence: 99%